Budaya Mutu dan Kepemimpinan Kristen Partisipatif dalam Mengatasi Krisis Literasi di NTT - Yuliana Boiliu; Hotmaulina Sihotang; Erni Murniati (Sekolah Tinggi Teologi SAPPI Ciranjang, 2026)
The literacy crisis in East Nusa Tenggara (NTT) reflects structural challenges that extend beyond low reading interest, encompassing educational, social, cultural, and economic factors. Limited access to reading materials, disparities in teacher capacity, linguistic transitions, and inadequate digital infrastructure continue to hinder literacy development. This study examines how the integration of Total Quality Management (TQM) and participatory Christian leadership can strengthen literacy initiatives in NTT. TQM provides a systematic framework for continuous quality improvement through planning, implementation, evaluation, and stakeholder involvement. Complementing this approach, participatory Christian leadership fosters collaboration among principals, teachers, parents, and local communities in developing culturally relevant and community-based literacy programs. The synergy between quality culture and participatory leadership promotes sustainable, low-cost, and context-sensitive literacy interventions. The study concludes that improving literacy in NTT requires not only educational resources but also organizational transformation, community participation, and collaborative leadership to achieve inclusive and sustainable educational development.